2008
DOI: 10.1017/s1368980008001705
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent comparison of energy intake and expenditure among adults in Butajira District, Ethiopia

Abstract: Objective: To estimate and compare dietary energy intake (DEI) and total energy expenditure (TEE) among adults, using questionnaires. Design: Comparative, cross-sectional study. Setting: Community-based, at the demographic surveillance site (DSS) in Butajira District of Ethiopia. Subjects: A total of 619 adults, 18-64 years of age, were randomly selected from among the urban and rural population of Butajira using the DSS sampling frame. Habitual dietary intake and physical activity were assessed using question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Among females, 19.6% were overweight and 7.1% were obese, whereas among males, 25.7% were overweight and only 3% were obese. The cutoff points used for classification of participants as overweight and obese were similar to those introduced by the WHO [14]. Waist circumference was higher in males than females (P < 0.05) but hip circumference was higher in females (Table2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among females, 19.6% were overweight and 7.1% were obese, whereas among males, 25.7% were overweight and only 3% were obese. The cutoff points used for classification of participants as overweight and obese were similar to those introduced by the WHO [14]. Waist circumference was higher in males than females (P < 0.05) but hip circumference was higher in females (Table2).…”
Section: Resultsmentioning
confidence: 99%
“…Data were collected by face-to-face interview using a structured Food Frequency Questionnaire (FFQ) modified from the Helen Keller International FFQ that was used previously in Ethiopia, to estimate meat and vegetable consumption that was in addition to the staple food intake [14]. The FFQ included eight food categories (Meat, Egg, Fish, Fat rich food, Vegetables, Fruits, Diary products, Sweet food) and was designed to obtain qualitative information about the usual food consumption patterns with an aim to assess the frequency with which certain food items or groups are consumed during a specific time period [15].…”
Section: Methodsmentioning
confidence: 99%
“…Using a questionnaire for total energy expenditure and dietary diary for energy intake, Kim and Cha [25] reported that the surveyed total energy expenditure levels for overweight middle-aged women was 3,256.8 kcal·day -1 , while energy intake was 2,080.2 kcal·day -1 , which showed a large comparative difference (-1,176.6). However, Tesfaye et al [26] used a survey to measure total energy expenditure, which was 1,925 kcal·day -1 , and a dietary diary to measure energy intake, which was 1,720 kcal·day -1 . These values differ by -205 kcal·day -1 , which is similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Each method has its own utilities and limits in terms of accuracy, cost, versatility and practicality in free-living situations for the evaluation of average daily energy expenditure (EE) and dose-response associations with health outcomes based on recommended PA or EE cut-off points (17,18) . Although simplified and relatively cheap versions of the heart-rate monitoring (HRM) technique have been devised to be used in epidemiological investigations (19,20) , a specific usefulness of the PAQ method is that it also provides detailed quantitative and qualitative assessment of the entire spectrum of activity and inactivity (21)(22)(23)(24)(25)(26) allowing a variety of analysis purposes, e.g. habitual PA patterns (27) .…”
mentioning
confidence: 99%